The switch - Brown, Sandra, 1948- (New York : Warner Books, 2000)
On a lark, twin sisters decide to switch places for an evening. When one is murdered, the other is soon on the run.
Keywords: Twins -- Fiction; Sisters -- Fiction; Revenge -- Fiction; Mystery fiction